2021
DOI: 10.1186/s12885-021-08499-9
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate carboxylase promotes thyroid cancer aggressiveness through fatty acid synthesis

Abstract: Background Pyruvate carboxylase (PC) is an important anaplerotic enzyme in the tricarboxylic acid cycle (TCA) in cancer cells. Although PC overexpression has been observed in thyroid cancer (TC), the mechanisms involved in the carcinogenic effects of PC are still unclear. Methods Bioinformatics analysis and clinical specimens were used to analyze the relationship of PC expression with clinicopathological variables in TC. Fatty acid synthesis was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Moreover, PC was discovered to promote BC metastasis [ 59 , 62 ]. Liu et al [ 63 ] reported that PC could activate the AKT/mTOR pathway in thyroid cancer cells. In the last few years, some literatures have reported the regulatory role of lncRNAs in PC expression in cancer cells [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PC was discovered to promote BC metastasis [ 59 , 62 ]. Liu et al [ 63 ] reported that PC could activate the AKT/mTOR pathway in thyroid cancer cells. In the last few years, some literatures have reported the regulatory role of lncRNAs in PC expression in cancer cells [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using the HT-29 colon cell line to represent a highly invasive CRC cell line in vivo ( 31 ), we showed that PC KO HT-29 cell lines displayed a marked reduction of proliferation throughout the whole time-course of the assay. This phenotypic defect was similarly reported in PC-deficient cancers such as glioblastoma ( 18 ), MDA-MB-231 breast cancer ( 16 ), non-small cell lung cancer ( 14 ), papilloma thyroid carcinoma ( 19 , 32 ), and ovarian cancer ( 33 ). The marked increase of apoptotic cells and PARP cleavage indicates that apoptosis is at least in part responsible for the growth inhibition of PC KO HT-29 cells.…”
Section: Discussionsupporting
confidence: 65%
“…The decrease in lipid synthesis can potentially affect these structures, limiting the motility of cancer cells (39, 40). Liu et al (32) have recently reported that the PC knockdown-papillary thyroid cancer lines, PTC1, also showed a marked decrease of cell motility accompanied by reduced fatty acid synthesis and downregulation of expression of FASN but not ACC1. Although the reduction of FASN expression was associated with decreased expression of SREBP1c, a transcriptional regulator of the FASN gene, it is still unclear how depletion of oxaloacetate results in down-regulation of SREBP1c expression in PC knockdown PTC1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in FA levels was observed as a further consequence of PC upregulation in PTC associated with tumor progression. In particular, PC induces the Akt/mTOR signaling pathway, thus, upregulating SREBP1c, which, in turn, upregulates FASN and, consequently, lipogenesis and EMT ( Figure 4 ) [ 198 ]. PC ↑ ⇒ SREBPc ↑ ⇒ FASN ↑ ⇒ FAs↑ ⇒ ZEB1, SNAIL ↑ ⇒ EMT …”
Section: Emt and Metabolism In Selected Cancersmentioning
confidence: 99%